(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Nutrition care in hospital is an essential part of patient care. Good nutrition care encourages patients to eat well, giving them nutrient as they need to achieve from surgery or illness. The need for dietician resources in nutrition department is required to assure quality nutritional care for patients. This study’s goal is to analysis dietitian manpower needs for inpatient based on nutritionist is workload. This study has been held from March to May 2004. There were five steps to calculate dietitian manpower needs: time available during a year, dietitians main job, load of each main job, standard for miscellaneous time (meeting, rest, praying) and the quantity of dietitian main job. The result showed that time available during a year was 1655 hours. Workload of clinical dietitian was divided into nine major activities. The result indicated that their activities were mostly spent for direct patient care. The calculation of dietitian needed for inpatients (internal unit, pediatric unit, surgery unit, VIP unit, etc) were fourteen. The number of dietitians manpower for inpatient in Sardjito General Hospital had meet the need based on their workload.